The Structure of The Poetic Image In (Mustefa Beg Kurdi)’ Poetry - Lana Radwan Abbas; Jabbar Ahmed Hussein (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Mustafa Bey Kurdi, one of the founders of classical Kurdish poetry - the middle dialect, given that poetry is written on 3 foundations (poetic music, poetic language, and poetic image). The first is the nature and components of the image. Second, the identification of the sources that the poet benefits from in designing images is one of the most prominent results that we obtained through this research.